2020
DOI: 10.1371/journal.pone.0241895
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mental health during the Covid-19 pandemic in the US: Role of economic concerns, health worries and social distancing

Abstract: Despite the profound health and economic implications of Covid-19, there is only limited knowledge to date about the role of economic concerns, health worries and social distancing for mental health outcomes during the pandemic. We analyze online survey data from the nationally representative “Understanding America Study” (UAS) covering the period of March 10-31st 2020 (sample size: 6,585). Mental health is assessed by the validated PHQ-4 instrument for measuring symptoms of depression and anxiety. About 29% (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
121
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 38 publications
13
121
2
3
Order By: Relevance
“…For example, a study of 5065 US adults in March indicated that among the states with more than 50 COVID-19 cases, each additional day was associated with a 11% increase in the odds of moving up a category of psychological distress. 5 Another March 2020 study of 9687 Americans with no prior history of a mental health condition asked about psychological distress within the past week (compared to this study of past 2 weeks experience) and found that the major symptoms of psychological distress experienced for at least 3 days in the past week were feeling nervous, anxious or on edge (39%) and feelings of depression (19%). 13 Despite the variation in scales/measures and study period, across most studies, anxiety was more common than depression in the US population (a finding that is confirmed in this study).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…For example, a study of 5065 US adults in March indicated that among the states with more than 50 COVID-19 cases, each additional day was associated with a 11% increase in the odds of moving up a category of psychological distress. 5 Another March 2020 study of 9687 Americans with no prior history of a mental health condition asked about psychological distress within the past week (compared to this study of past 2 weeks experience) and found that the major symptoms of psychological distress experienced for at least 3 days in the past week were feeling nervous, anxious or on edge (39%) and feelings of depression (19%). 13 Despite the variation in scales/measures and study period, across most studies, anxiety was more common than depression in the US population (a finding that is confirmed in this study).…”
Section: Discussionmentioning
confidence: 77%
“…These numbers closely resemble the US population distribution as per the census and labor statistics, making our study sample representative of the US population to a great extent. 4 , 5 , 24…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More precisely, it was shown that the burden of measures designed to stem the pandemic are unevenly distributed across sociodemographic groups and, therefore, it is necessary to shed light on what behavior can be expected of different segments of the population during a pandemic given heterogeneity in the incentives, constraints and circumstances people face [ 33 ]. Moreover, as showed before, high expected probability of running out of money is positively associated with mental health score, while perceived risks of dying from Covid-19 and social are also strongly correlated with higher levels of depression/anxiety [ 49 ]. Therefore, as the number of cases continues to rise, public-health politics may consider not only sensitizing people regarding infection rates, but also by providing health information and services, financial incentives, or fiscal alternatives so that people can maintain their businesses in a sustainable way.…”
Section: Discussionmentioning
confidence: 93%